Case Report: Molecular and microenvironment change upon midostaurin treatment in mast cell leukemia at single-cell level - Liu, Meng-Ke; Liu, Feng; Dai, Yu-Ting; Weng, Xiang-Qin; Cheng, Li-Li; Fan, Li-Quan; Liu, Han; Jiang, Lu; Sun, Xiao-Jian; Fang, Hai; Wang, Li; Zhao, Wei-Li (Frontiers in Immunology, 2023)
Mast cell leukemia is a rare and aggressive disease, predominantly with KIT D816V mutation. With poor response to conventional poly-chemotherapy, mast cell leukemia responded to the midostaurin treatment with a 50% overall response rate (ORR), but complete remission rate is approximately 0%. Therefore, the potential mechanisms of midostaurin resistance and the exact impacts of midostaurin on both gene expression profile and mast cell leukemia microenvironment in vivo are essential for design tailored combination therapy targeting both the tumor cells and the tumor microenvironment. Here we report a 59-year-old male mast cell leukemia patient with KIT F522C mutation treated with midostaurin.Single-cell sequencing of peripheral blood and whole exome sequencing (WES) of bone marrow were performed before and 10 months after midostaurin treatment. In accordance with the clinical response, compared to the pretreatment aberration, the decline of mast cells and increase of T-, NK, B-cells in peripheral blood, and the decrease of the KIT F522C mutation burden in bone marrow were observed. Meanwhile, the emergence of RUNX1 mutation, upregulations of genes expression (RPS27A, RPS6, UBA52, RACK1) on tumor cells, and increased frequencies of T and NK cells with TIGIT, CTLA4, and LAG3 expression were observed after midostaurin treatment, predicting the disease progression of this patient. As far as we know, this is the first case reporting the clinical, immunological, and molecular changes in mast cell leukemia patients before and after midostaurin treatment, illustrating the in vivo mechanisms of midostaurin resistance in mast cell leukemia, providing important clues to develop a sequential option to circumvent tumor progression after targeting oncogene addiction and prolong patients' survival.